Study of Perceptual Sensory Disorders : A Case Study of Schizoaffective Patient - Uyun Dwiranto; Nunung Rachmawati; Sutedjo (Health Media, 2021)
There are 2% to 9% general populations in the United States of America hospitalized due to schizoaffective disorders. Hallucination is a schizoaffective symptom. Based on the Grhasia Yogyakarta mental hospital file in the last 3 years there were 2723 (19,7 %) patients who experienced sensory perception disorders: hallucinations/illusion. Patients with hallucinations if left untreated can injure themselves and others, ineffective individual handling, interpersonal disorder withdraws, self-care disorder. This documentation study was conducted to evaluate the characteristics and implementation of nursing care in patients with auditory hallucination. This documentation study uses a descriptive qualitative methode that describes a case by utilizing a nursing case report in 2017. The results showed that the patient often listened to voices, talked to himself, and suddenly laughed. The problem of sensory perception was impaired. The auditory hallucinations were partially resolved. The description of sensory perception disorder was obtained after observation.